2010
DOI: 10.2119/molmed.2010.00015
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholinesterase Activities Distinguish between Stroke Patients and Controls and Predict 12-Month Mortality

Abstract: To date there is no diagnostic biomarker for mild stroke, although elevation of inflammatory biomarkers has been reported at early stages. Previous studies implicated acetylcholinesterase (AChE) involvement in stroke, and circulating AChE activity reflects inflammatory response, since acetylcholine suppresses inflammation. Therefore, carriers of polymorphisms that modify cholinergic activity should be particularly susceptible to inflammatory damage. Our study sought diagnostic values of AChE and Cholinergic St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
68
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 29 publications
13
68
1
Order By: Relevance
“…Acetylcholine esterase (AChE) activity has been found higher in cerebrospinal fluid of acute stroke patients compared with healthy controls [66]. Recently, lower serum AChE activities have been found in acute stroke patients compared with controls, and those patients who died after a 12-month follow-up period were found to have lower AChE activities than survivors in the same study [67]. Whether the role of AChE as a marker of the PSNS activity could predict specific post-stroke complications is under investigation.…”
Section: Hormones Of the Psnsmentioning
confidence: 87%
“…Acetylcholine esterase (AChE) activity has been found higher in cerebrospinal fluid of acute stroke patients compared with healthy controls [66]. Recently, lower serum AChE activities have been found in acute stroke patients compared with controls, and those patients who died after a 12-month follow-up period were found to have lower AChE activities than survivors in the same study [67]. Whether the role of AChE as a marker of the PSNS activity could predict specific post-stroke complications is under investigation.…”
Section: Hormones Of the Psnsmentioning
confidence: 87%
“…Assays were performed in 0.1 M phosphate buffer, pH 7.4, 0.5 mM dithio-bis-nitrobenzoic acid and 1 mM acetylthiocholine substrate at room temperature [19]. Optical density at 405 nm was monitored for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…In their study, low CHE was a significant predictor of mortality and thus included in a multivariable risk score that demonstrated an excellent discriminatory power for 10-year survival. Ben Assayag et al 13 reported lower CHE activity in 264 patients with an ischemic stroke compared to healthy controls and found very low CHE activity to be a predictor of mortality in their patient population. The above-described findings together with our observations suggest that cholinergic imbalance affects long-term prognosis in healthy individuals as well as in patients with manifest cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%